Prospek Budidaya dan Analisis Usaha Tanaman Sereh Wangi di Wilayah KPH Kayutangi Kabupaten Banjar - Lifia Mahlita Soraya; Rusmin Nuryadin (PPJP Universitas Lambung Mangkurat, 2022)
The objectives of this study are : (1) The economic value of citronella farming in the Kayutangi KPH Area, Banjar Regency, and (2) Obstacles to lemongrass farming in terms of cultivation post-harvest handling in KPH Kayutangi, Banjar Regency. Methode of this study is Quantitative and used 14 respondents, namely ten managers and members of farmer groups, 3 FMU officers, and one CV representative. Nusantara Asri. Processing analysis in this study uses the method of income (TR) minus the total cost (TC) to analyze the profit of citronella farming. At the first harvest, the economic value of citronella farming in the KPH Kayutangi area of Banjar Regency is (minus) -Rp. Ten million seven hundred thirty-seven thousand due to the results of the distillation under SNI, as for the annual economic value (3 x harvest) if lemongrass cultivation is fully handed over to farmers to buy cultivation needs directly on the market with the assumption that the distillation results are following SNI standards, then 2 hectares of land will generate a profit of Rp. 92.281.000, while if the distillation results are under SNI, they still get a profit of Rp. 19.321.000.